A influência das relações de gênero na divisão de tarefas familiares e na violência entre parceiros íntimos - Bertho, Maria Alice Centanin (2020)
Issues of gender inequality and its consequences for women are widely discussed today. In the family context, these issues are present and are evidenced by the lack of equity in the distribution of domestic work and parenting among spouses and violence between intimate partners. It is understood that gender inequalities are maintained by gender stereotypes perpetuated socially and in the family. The present study has the general objective of identifying individual, family and marital aspects present in the interaction of heterosexual couples based on a gender analysis. Specific objectives are considered: (1) to verify prescriptive gender stereotypes in individuals of both sexes; (2) to verify how individuals of both sexes perceive the division of domestic tasks and parenting; (3) to compare the differences in involvement, according to gender, regarding the type of household and parenting tasks (practical and management); (4) verify the indicators of violence between intimate partners; (5) check indicators of well-being (quality of life, self-esteem, marital satisfaction); (6) verify the correlation of prescriptive gender stereotypes with the other variables evaluated: (a) division of domestic tasks and parenting and (b) indicators of violence between intimate partners. 130 individuals participated (102 women and 28 men), aged between 18-60 years (M = 35.92; SD = 9.32), who worked in a paid job, lived in the same house and were in a heterosexual relationship. Participants answered an online form containing the following instruments: Criterion Brazil; Revised conflict tactics scales - CTS2; Scale of gender roles; WHOQOL-bref (World Health Organization Quality of Life - short version); Rosemberg self-esteem scale; Scale of emotional support received from the spouse; Scale of division of domestic tasks and parenting. Descriptive analyzes of the data were performed based on the calculation of mean and standard deviation and frequency analyzes. The comparison between means of the groups (men and women) was performed using the Mann-Whitney test and the frequency comparisons using Fisher's exact test and Chi-square test. The characterization data showed that 89.2% of the participants are part of the economic classification classes A, B1 and B2, 70.8% were married and 53.8% had a child (ren). The results indicated that there are differences between the perception of men and women regarding the division of family tasks, and that they indicate carrying out activities more frequently while men stated that they share them equally with their partner, especially for parenting tasks. The difference between practical and management tasks also demonstrated such a difference between genders. There was no statistically significant difference for IPV measurements. Regarding well-being indicators, women had a lower average psychological domain. Considering participants with and without children, the difference was significant for the physical domain, lower for fathers / mothers. Regarding satisfaction with the relationship, the average of women - especially mothers - was the lowest observed, with a significant difference. The results demonstrate differences between genders in the family environment, accentuating an accumulation of functions for women, especially mothers, which can have consequences for mental health. The management of family tasks proved to be a relevant aspect in relation to task sharing.